Food insecurity in the context of HIV/AIDS: A framework for a new era of programming - Frega, Romeo; Duffy, Francesca; Rawat, Rahul; Grede, Nils (SAGE Publications, 2010)
Food insecurity can be both a consequence and a driver of HIV/AIDS. It is often difficult to disentangle these two roles of food insecurity, since the HIV epidemic has different drivers in different settings. The advent of antiretroviral treatment in resource-limited settings adds an additional layer of complexity. This paper seeks to organize current thinking by reviewing the existing literature on food insecurity and HIV/AIDS and describing the complex interactions between them.Based on literature review, the paper proposes a framework to understand the linkages, distinguishing four types of interventions to address them. It is hoped that the model, albeit simplified as is any framework, will help to structure research, policy, and programming in the field of HIV/AIDS and food insecurity. Finally, the paper intends to widen the lens to regard food not just as a means to provide calories or an income transfer but also as a carrier of adequate nutrition in the context of HIV.An adequate response to HIV/AIDS and food insecurity must be tailored to specific settings. Interventions distinguished in this paper are aimed at both promoting food security and providing antiretroviral treatment and nutrition support. The four types of interventions are containing HIV and preventing AIDS through comprehensive treatment regimes that include nutritional support; mitigating the effects of AIDS through support; providing HIV-sensitive, but not HIV-exclusive, safety nets at the individual, household, and community levels; and limiting the exposure to risk through HIV prevention activities.